The Effect of Effleurage Massage on Reducing Back Pain in the Third Trimester Pregnant Women in the Guidance Area of Gunungpati Public Health Centre - Yuni Astuti; Fitri Wahyuni; Tuti Anggarawati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Pregnancy in the third trimester often causes discomfort for expectant mothers, including back pain. This pain, typically located in the lumbosacral area, arises from the growing uterus, which alters posture and increases pressure on the spinal curvature. As the abdominal muscles stretch to accommodate the enlarging uterus, muscle fatigue and increased spinal load contribute to back pain. Effleurage massage, a non-pharmacological therapy involving gentle stroking movements, may help alleviate this discomfort. The massage technique stimulates and relaxes tense nerves and muscles. This study aimed to analyze the effect of effleurage massage on reducing back pain in third-trimester pregnant women. A quasi-experimental research method with a one-group pre-test-post-test design was employed. Participants were recruited using total sampling. The results showed a significant difference in back pain scores before and after effleurage massage (p = 0.000). This study concludes that effleurage massage has a significant effect on reducing back pain in pregnant women in the third trimester.